Wettability and surface roughness analysis of Laser Surface Texturing of AISI 430 stainless steel - Moldovan, Edit Roxana; Concheso Doria, Carlos; Ocaña, Jose Luis; Baltes, Liana Sanda; Stanciu, Elena Manuela; Croitoru, Catalin; Pascu, Alexandru; Tierean, Mircea Horia (MDPI Materials)
Due to its wide applicability in industry, devising microstructures on the surface of materials can be easily implemented and automated in technological processes. Laser Surface Texturing (LST) is applied to modify the chemical composition, morphology, and roughness of surfaces (wettability), cleaning (remove contaminants), reducing internal stresses of metals (hardening, empering), surface energy (polymers, metals), increasing the adhesion (hybrid joining, bioengineering) and decreasing the growth of pathogenic bacteria (bioengineering). This paper is a continuation and extension of our previous studies in laser-assisted texturing of surfaces. Three different patterns (crater arraytype C, two ellipses at 90 overlapping with its mirror-type B and 3 concentric octagons-type A) were applied with a nanosecond pulsed laser (active medium Nd: Fiber Diode-pumped) on the surface of a ferritic stainless steel (AISI 430). Micro texturing the surface of a material can modify its wettability behavior. A hydrophobic surface (contact angle greater than 90 ) was obtained with different variations depending on the parameters. The analysis performed in this research (surface roughness, wettability) is critical for assessing the surface functionality, characteristics and properties of the stainless steel surface after the LST process. The values of the surface roughness and the contact angle are directly proportional to the number of repetitions and inversely proportional to the speed. Recommendations for the use of different texturing pattern designs are also made.
Keywords: surface roughness; wettability; surface laser texturing; surface patterning; ferritic stainless steel